Educação de jovens e adultos no contexto do direito humano a educação: um estudo sobre o Grupo de Trabalho N 18 da Associação Nacional de Pós-Graduação em Educação – ANPED - Siqueira, Adson Matheus Lucas (2021)
This research aims to analyze the challenges and perspectives of human rights education in the context of youth and adult education through the study of the working group18 of the National Association of Graduate Studies in Education - ANPEd. For this, we adopted the concept of education from the theoretical perspective of Paulo Freire, which aims to enable the individual to be freed from injustice and oppressive reality through awareness. The male and female students participating in the Youth and Adult Education modality had their right to education infringed as they were unable to become literate or complete their schooling process at the so called appropriate age. Education in Human Rights enables students of Youth and Adult Education to have a new vision of human rights, leading them to realize that such rights contribute to the knowledge of their dignity and their status as subjects of rights. In this way, it is opportune to investigate the research presented in WG No. 18, at the ANPEd meeting, held in 2018, direct reflections of the current understanding, both academic and social, on the education of young and adult people and their contributions to the feeling, thinking and acting on public policies in human rights education in the education of young people and adults. Thus, a qualitative approach is adopted, the instruments for data generation are bibliographic and documental research and the data will be analyzed in the light of the set of techniques called content analysis. It is concluded that there are still, currently, a considerable number of researchers in the area who can, gathered in national networks, institutionally integrate ANPEd's performance and, through WG 18, contribute to it by providing new directions for the education of young people, adults and elderly taking as a foundation the valuable learnings offered by Education in Human Rights, which reveals itself as a valuable ally in facing various educational problems that continue to affect Youth and Adult Education, such as: the absence or low investment by the public administration ; the lack of both initial and continued training of educators; inequality; the evasion; the juvenilization of the public; the scarcity of specific teaching equipment; the low self-esteem of students; the tiredness; insufficient time to pay attention to studies; methods used often inadequate that end up making learning difficult and increase several other challenges that are still not being faced.